2022
DOI: 10.1002/14651858.cd013638.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Community views on mass drug administration for filariasis: a qualitative evidence synthesis

Abstract: Background The World Health Organization (WHO) recommends mass drug administration (MDA), giving a drug at regular intervals to a whole population, as part of the strategy for several disease control programmes in low‐ and middle‐income countries. MDA is currently WHO policy for areas endemic with lymphatic filariasis, which is a parasitic disease that can result in swollen limbs and disability. The success depends on communities adhering to the drugs given, and this will be influenced by the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 98 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…People with late-stage LF were those with the physical conditions of hydrocoele and elephantiasis, they suffered the most from the disease and yet did not benefit from the treatment 31…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…People with late-stage LF were those with the physical conditions of hydrocoele and elephantiasis, they suffered the most from the disease and yet did not benefit from the treatment 31…”
Section: Resultsmentioning
confidence: 99%
“…Amidst the positive community impact, individual harms, notably adverse effects, have been highlighted in numerous publications. Those often receive insufficient attention within programmes, leaving individuals to cope individually and incur economic losses through direct treatment costs and lost labour time 31 32 36 41. These individual harms stand in contrast with collective benefits and they demand attention due to their significant burden on affected people.…”
Section: Discussionmentioning
confidence: 99%
“…We used a quality assessment tool adapted from one developed by the Evidence for Policy and Practice Information and Co-ordinating Centre (EPPI centre) 37 38. Although non-validated, it was chosen for its detailed signalling questions, prior use within the author team and use in several other well-conducted qualitative evidence syntheses, including those published by Cochrane 39–41. The Enhancing transparency in reporting the synthesis of qualitative research (ENTREQ) guideline for transparency was followed in the reporting of synthesis of qualitative research42 (online supplemental annexure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have identified barriers to drug LF implementation, including a lack of trust in DEC, fear of side effects, lack of drug distribution, forgetting to take the drug, becoming sick when DEC were given out, poor understanding, and individual direct experience. 2,3 To the best of our knowledge, there is limited evidence regarding the factors influencing drug compliance among LF-infected individuals, especially in Indonesia, although previous studies have demonstrated MDA compliance. We investigated factors associated with drug compliance among adult respondents diagnosed with LF over the past two years.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have identified barriers to drug LF implementation, including a lack of trust in DEC, fear of side effects, lack of drug distribution, forgetting to take the drug, becoming sick when DEC were given out, poor understanding, and individual direct experience. 2,3…”
Section: Introductionmentioning
confidence: 99%